Um homomorfismo índice associado à ações livres de grupos abelianos finitos - Ura, Sérgio Tsuyoshi (Universidade Federal de São Carlos, 2011)
The main objective of this work is to generalize an article of Pedro Pergher, specifically the article A Zp - index homomorphism for Zp-spaces - Houston J. Math. - 31 - (2005) - N. 2 - 305-314 [7], replacing the cyclic group Zp by any finite abelian group. In his article, P. Pergher constructed an index-homomorphism associated to Zp-spaces, that is, topological spaces X equipped with free actions of the cyclic group Zp. This homomorphism has as domain the equivariant homology of X with Zp-coefficients, and Zp as target space. Our construction extends the construction of P. Pergher for arbitrary finite abelian groups G, in such a way that, similarly, our homomorphism has the equivariant homology of X with G-coefficients as domain, and G as target space. When restricted to G = Zp, our construction coincides with the Pergher index. It will be seen that our homomorphism allows achieving a Borsuk-Ulam result, concerning the existence of equivariant maps connecting two G-spaces subject to certain topological and homological conditions, when G has 2q elements with q odd. In the last chapter of the work, we detail a very recent result of Ikumitsu Nagasaki, Tomohiro Kawakami, Yasuhiro Hara and Fumihiro Ushitaki, which also proves our result of Borsuk-Ulam type above mentioned, using the Smith homology, and in such a way that all values of p are covered.
Keywords: Topologia algébrica; ZP - índice; Teoremas do tipo Borsuk-Ulam; G-índice; CIENCIAS EXATAS E DA TERRA::MATEMATICA